2017
DOI: 10.1155/2017/9080869
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mechanisms of Diabetic Atherosclerosis: Herbal Medicines as a Potential Therapeutic Approach

Abstract: An increasing number of patients diagnosed with diabetes mellitus eventually develop severe coronary atherosclerosis disease. Both type 1 and type 2 diabetes mellitus increase the risk of cardiovascular disease associated with atherosclerosis. The cellular and molecular mechanisms affecting the incidence of diabetic atherosclerosis are still unclear, as are appropriate strategies for the prevention and treatment of diabetic atherosclerosis. In this review, we discuss progress in the study of herbs as potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 129 publications
0
10
0
Order By: Relevance
“…AS is a primary instigator of coronary artery disease and manifests itself in other conditions including cerebrovascular disease as well as cardiovascular events such as myocardial infarctions, all of which are accompanied by high mortality and morbidity worldwide (Mach et al, 2008;Rader and Daugherty, 2008). Although several therapeutic approaches can be employed for the treatment of AS, there are subgroups of high risk patients who fail to benefit from existing treatment modalities (Ren et al, 2017;Tian et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…AS is a primary instigator of coronary artery disease and manifests itself in other conditions including cerebrovascular disease as well as cardiovascular events such as myocardial infarctions, all of which are accompanied by high mortality and morbidity worldwide (Mach et al, 2008;Rader and Daugherty, 2008). Although several therapeutic approaches can be employed for the treatment of AS, there are subgroups of high risk patients who fail to benefit from existing treatment modalities (Ren et al, 2017;Tian et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The increased prevalence of diabetes mellitus is considered one of the greatest public health challenges nowadays. Type 1 diabetes mellitus (T1DM), a polygenic autoimmune disease, is resulted from both genetic and environmental factors [ 1 ]. Although T1DM has a lower prevalence compared with type 2 diabetes mellitus (T2DM), it is the most common form of diabetes in childhood and has a greater impact on the quality of living life.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous clinical studies showed that patients with hyperglycemia are more prone to AS-related diseases [109], and blood glucose therapies effectively prevent cardiovascular diseases [110]. Hyperglycemia-linked endothelial dysfunction may correlate with increased vascular permeability, upregulation of adhesion molecules, chemokines, and ROS [111,112]. Hyperglycemia also contributed to the atherogenic modification of LDL and triggered the pathological accumulation of lipids in AS plaque [113].…”
Section: Hyperglycemiamentioning
confidence: 99%